DDAVP Reduces Bleeding during Continued Hirudin Administration in the Rabbit - Bove, Christina M; Casey, Brenda; Marder, Victor J (Thrombosis and Haemostasis, 1996)
Hirudin is a potent thrombin inhibitor derived from the leech Hirudo medicinalis salivary gland which has considerable potential for therapeutic use in thrombotic disease. The major risk attendant its use is hemorrhage. This study investigates the hypothesis that the prohemostatic effects of DDAVP infusion can curtail the hemorrhagic effect induced by ongoing hirudin administration.In a randomized and blinded manner, rabbits were exposed to a 15-min intravenous infusion of DDAVP or saline midway through a continuous two-h intravenous infusion of hirudin. Bleeding time was monitored by full thickness ear punctures performed before, during and after hirudin exposure.Hirudin induced a significant hemorrhagic state, manifest as a 7-10-fold prolongation of the primary bleeding time. DDAVP reduced the mean duration of primary bleeding from 10.8 min to 5.9 min (p = 0.001) as well as the number of sites which bled for longer than 6 or 20 min (46% vs 27%, p = 0.002; and 18% vs 5%, p = 0.002, respectively). Although there was no difference in the incidence of spontaneous rebleeding from these sites (44 vs 36%, p = 0.21), rebleeding did not persist as long in animals that received DDAVP (8 vs 16 min, p = 0.005), and fewer sites rebled for longer than 20 min (8 vs 27%, p = 0.027). Results were essentially the same for two different commercial recombinant hirudin preparations.DDAVP appears to attenuate the bleeding caused by continuous hirudin infusion in rabbits and establishes a foundation for clinical assessment in patients.